Pengaruh work-Life balance dan pengembangan karir terhadap loyalitas karyawan dengan kepuasan kerja sebagai variabel moderasi - Azzahra, Kania Najmi; Mapuasari, Supeni Anggraeni (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2025)
Employee loyalty is an important factor in achieving organizational success. Employees who show their dedication have the motivation to achieve organizational goals. The purpose of this study was to determine the effect of the independent variables work-life balance and career development on employee loyalty with job satisfaction as moderator. This quantitative research uses questionnaires and snowball sampling techniques. The sample consists of private employees. The findings show that work-life balance variables have a positive but statistically insignificant influence on employee loyalty variables. Career development variables have a positive and significant influence on employee loyalty. Job satisfaction strengthens the relationship between career development and employee loyalty.